Good wives - Alcott, Louisa M.; Collins, Anne (Oxford : Macmillan Heinemann ELT, 2005)
Good Wives continues the story of the March sisters, Meg, Jo, Beth and Amy, as they approach womanhood. Meg longs to begin her new life with John Brook, though they can never be rich; Jo returns to devote herself to literature, and to Beth, whose illness has left her weak but whose serenity shines through the household; and Amy has gone to Aunt March, bribed with the offer of drawing lessons. Laurie remains irrepressible, with his high spirits and sense of fun, though his pursuit of Jo's affections seems unlikely to succeed.